Development of tumor mutation burden as an immunotherapy biomarker: utility for the oncology clinic - Chan, Timothy A.; Yarchoan, M.; Jaffee, E.; Swanton, C.; Quezada, S. A.; Stenzinger, Albrecht; Peters, S. (Annals of oncology, 2019)
AbstractBackground. Treatment with immune checkpoint blockade (ICB) with agents such as anti-programmed cell death protein 1 (PD-1), anti-programmed death-liga
Published: 05 November 2018
Gesehen am 25.06.2019